2022
DOI: 10.1051/parasite/2022027
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and seasonal abundance of Culicoides (Diptera, Ceratopogonidae) in Shizong County, Yunnan Province, China

Abstract: Culicoides (Diptera, Ceratopogonidae) are small biting midges, some of which are vectors for animal associated arboviruses such as bluetongue virus (BTV) and Akabane virus (AKAV). BTV and AKAV are both pathogenic for livestock, with BTV in particular posing a major threat to domestic ruminants. Ongoing problems with BTV in ruminants in Shizong County of Yunnan Province, China, promoted a year-long investigation of the Culicoides in Shizong to determine relative abundance and seasonality of midges and to attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Culicoides are small biting midges with blood-sucking abilities in the family Ceratopogonidae (Diptera: Culicomorpha). Currently, there are 1347 species in the world and 480 species in China [1,2]. The female adults of many species of biting midges are pests of both people and livestock, causing painful lesions and inducing acute allergic reactions such as common summer eczema in horses [3].…”
Section: Introductionmentioning
confidence: 99%
“…Culicoides are small biting midges with blood-sucking abilities in the family Ceratopogonidae (Diptera: Culicomorpha). Currently, there are 1347 species in the world and 480 species in China [1,2]. The female adults of many species of biting midges are pests of both people and livestock, causing painful lesions and inducing acute allergic reactions such as common summer eczema in horses [3].…”
Section: Introductionmentioning
confidence: 99%
“…The climate in this region is tropical to subtropical in the south with high temperatures, heavy rain, and high humidity. Yunnan Province has a diverse range of Culicoides vectors (at least 36 species) [ 6 ], which facilitates the spread of arboviruses [ 7 ]. Previous studies reported the detection or isolation of several arboviruses, including bluetongue virus (BTV) [ 8 ], Tibet orbivirus (TIBOV) [ 9 ], and Banna virus (BAV) [ 10 ] from Culicoides in Yunnan Province.…”
Section: Introductionmentioning
confidence: 99%